Validation of Quantitative Scores Derived From Motor Evoked Potentials in the Assessment of Primary Progressive Multiple Sclerosis: A Longitudinal Study - Hardmeier, Martin; Schindler, Christian; Kuhle, Jens; Fuhr, Peter (Frontiers in Neurology, 2020)
Objective: To evaluate the sensitivity to change of differently calculated quantitative scores from motor evoked potentials (MEP) in patients with primary progressive multiple sclerosis (PPMS). Methods: 20 patients with PPMS had MEP to upper and lower limbs at baseline, years 1 and 2 measured in addition to clinical assessment (expanded disability status scale (EDSS), ambulation score); a subsample (n=9) had a nine-hole-peg-test (NHPT) and a timed-25-foot-walk (T25FW). Quantitative MEP scores for upper limbs (qMEP-UL), lower limbs (qMEP-LL) and all limbs (qMEP) were calculated in three different ways, based on z-transformed central motor conduction time (CMCT), shortest cortico-muscular latency (CxM-sh) and mean CxM (CxM-mn). Changes in clinical measures and qMEP-metrics were analysed by repeated measures ANOVA and a factor analysis was performed on change in qMEP-metrics. Results: EDSS and ambulation score progressed in the rANOVA-model (p<0.05; post-hoc comparison baseline-year2, p<0.1). Lower limb and combined qMEP-scores showed significant deterioration of latency (p<0.01, MEP-LL_CxM-sh: p<0.05) and in post-hoc comparisons (baseline-year2, p<0.05), qMEP_CxM-mn even over one year (p<0.05). Effect sizes were higher for qMEP-scores than for clinical measures, and slightly but consistently higher when based on CxM-mn compared to CxM-sh or CMCT. Subgroup analysis yielded no indication of higher sensitivity of timed clinical measures over qMEP-scores. Two independent factors were detected, the first mainly associated with qMEP-LL, the second with qMEP-UL, explaining 65% and 29% of total variability, respectively. Conclusions: Deterioration in qMEP-scores occurs earlier than EDSS progression in patients with PPMS. Upper and lower limb qMEP-scores contribute independently to measuring change, and qMEP-scores based on mean CxM are advantageous. The capability to detect subclinical changes longitudinally is a unique property of EP and complementary to clinical assessment. These features underline the role of EP as candidate biomarkers to measure effects of therapeutic interventions in PPMS.